The effect of basicity of modified ground granulated blast furnace slag on its denitration performance. (10th July 2021) - Zhang, Lei; Jia, Yang; Shu, Hao; Zhang, Lei; Lu, Xi; Bai, Fang; Zhao, Qianyu; Tian, De
Abstract: Blast furnace slag (BFS), a large amount of industrial solid waste, is currently used to make mainly concrete and building bricks. There is no doubt that it is a waste of rich elements and oxides in the slag. In order to increase the utilization and use value of BFS, this article prepared it as a denitration catalyst. The alkaline oxides CaO, MgO and the acidic oxides Al2 O3, SiO2 were used to modify the ground granulated blast furnace slag (GGBS). And it investigated the effect of the modified GGBS and alkalinity on denitration performance. Combining X-Ray fluorescence (XRF), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and scanning electron microscope (SEM) characterization, the results showed that: Alkaline oxides modified GGBS had good denitration performance, which benefited from –OH generated during the modification process. While acidic oxides modified GGBS hardly improved the denitration performance, because the acidic oxides would absorb the f-CaO in the slag. According to the calculation formula of slag alkalinity, the quaternary, ternary and binary alkalinity of 9 wt% MgO modified GGBS were 0.901, 1.262 and 1.089 respectively, and the denitration performance of the modified GGBS improved with the increase of alkalinity. Graphical abstract: Image 1 Highlights: Bentonite can be used as a binder to bond ground granulated blast furnace slag. Alkaline oxides modified catalysts have good denitration performance. Acidic oxides in the slag will reduce its denitration performance. The denitration of modified slag will increase with the increase of alkalinity.